Inositol 1,4,5-trisphosphate receptor/GAPDH complex augments Ca(2+) release via locally derived NADH - Patterson, Randen L. (National Academy of Sciences, 2005)
NADH regulates the release of calcium from the endoplasmic reticulum by modulation of inositol 1,4,5-trisphosphate receptors (IP(3)R), accounting for the augmented calcium release of hypoxic cells. We report selective binding of IP(3)R to GAPDH, whose activity leads to the local generation of NADH to regulate intracellular calcium signaling. This interaction requires cysteines 992 and 995 of IP(3)R and C150 of GAPDH. Addition of native GAPDH and NAD(+) to WT IP(3)R stimulates calcium release, whereas no stimulation occurs with C992S/995S IP(3)R that cannot bind GAPDH. Thus, the IP(3)R/GAPDH interaction likely enables cellular energy dynamics to impact calcium signaling.